The Influence Of Headmaster Controlling On Teacher Professionalism In Madrasah Tsanawiyah - Putri, Neti; Yuliharti, Yuliharti (Fakultas Tarbiyah dan Keguruan, 2024)
This study explores the impact of headmaster supervision on teacher professionalism in Islamic Junior High Schools (Madrasah Tsanawiyah). Using a correlational research design, the study evaluates two primary variables: headmaster supervision (X) and teacher professionalism (Y). The research aims to quantify the degree of influence exerted by headmaster supervision on teacher professionalism. A total population of 64 teachers from the selected schools was surveyed, ensuring comprehensive data collection through questionnaires and documentation. Data analysis employed percentage-based quantitative techniques and simple regression analysis.Findings reveal a significant positive correlation between headmaster supervision and teacher professionalism, with a correlation coefficient of 0.710, exceeding the critical value of 0.246 at a 5% significance level. The coefficient of determination (R²) indicates that headmaster supervision accounts for 50.4% of the variance in teacher professionalism, with the remaining 49.6% influenced by other unexplored variables. These results underline the pivotal role of effective headmaster supervision in enhancing teacher professionalism, thereby contributing to the overall quality of education.